2013
DOI: 10.1016/j.clinbiomech.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing carpal arch width to increase cross-sectional area of carpal tunnel — a cadaveric study

Abstract: Background Carpal tunnel morphology plays an essential role in the etiology and treatment of carpal tunnel syndrome. The purpose of this study was to observe the morphological changes of the carpal tunnel as a result of carpal arch width narrowing. It was hypothesized carpal arch width narrowing would result in increased height and area of the carpal arch. Methods The carpal arch width of eight cadaveric hands was narrowed by a custom apparatus and cross-sectional ultrasound images were acquired. The carpal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…These structural changes are likely related to the soft tissue components of the carpal tunnel boundary which provides the carpal tunnel with some degree of compliance [8, 1215]. Recent studies support that the cross-sectional area of the carpal tunnel can be increased by narrowing the carpal arch width (CAW), i.e., distance between the trapezium and hook of hamate [13, 14, 16, 17]. Geometric modeling [16] and in vitro [13, 16] studies have shown that CAW narrowing is associated with palmar bowing of the TCL which increases the height and cross-sectional area of the carpal arch.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These structural changes are likely related to the soft tissue components of the carpal tunnel boundary which provides the carpal tunnel with some degree of compliance [8, 1215]. Recent studies support that the cross-sectional area of the carpal tunnel can be increased by narrowing the carpal arch width (CAW), i.e., distance between the trapezium and hook of hamate [13, 14, 16, 17]. Geometric modeling [16] and in vitro [13, 16] studies have shown that CAW narrowing is associated with palmar bowing of the TCL which increases the height and cross-sectional area of the carpal arch.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies support that the cross-sectional area of the carpal tunnel can be increased by narrowing the carpal arch width (CAW), i.e., distance between the trapezium and hook of hamate [13, 14, 16, 17]. Geometric modeling [16] and in vitro [13, 16] studies have shown that CAW narrowing is associated with palmar bowing of the TCL which increases the height and cross-sectional area of the carpal arch. These changes may provide additional space within the carpal tunnel for its contents; however, such previous studies have not investigated the impact of CAW narrowing on the tunnel contents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to experimentation, each specimen was preconditioned by displacing the ridge of the trapezium by 2 mm in a set of the 14 directions; the order of the 14 directions was randomized within a set, and the preconditioning was repeated for 10 sets. A preconditioning magnitude of 2 mm was chosen because it is the largest displacement magnitude used for testing and the carpal arch remains relatively elastic within this amount of displacement (Gabra et al, 2012; Li et al, 2013; Xiu et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Experimental studies have investigated the uniaxial stiffness characteristics of the wrist in the medial-lateral (Fuss and Wagner, 1996; Xiu et al, 2010) and dorsal-palmar directions (Garcia-Elias et al, 1989a). The two-dimensional mechanics of the wrist have also been investigated with respect to the compliance of the carpal tunnel (Tung et al, 2010), force transmission across wrist (Garcia-Elias et al, 1989b; Schuind et al, 1995), and manipulation of the carpal tunnel's cross-sectional area (Li et al, 2013; Li et al, 2011; Li et al, 2009). Three-dimensional studies of the wrist structure have been mainly studied with computational modeling with a particular focus on force transmission across the carpus (Fischli et al, 2009; Guo et al, 2009; Majima et al, 2008; Majors and Wayne, 2011; Marquez-Florez et al, 2015; Matsuki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%